Recycling of sago (Metroxylon sagu) bagasse with chicken manure slurry through co-composting - Ch'ng, Huck Ywih; Ahmad, Osumanu Haruna; Kasim, Susilawati; Nik Majid, Nik Muhamad (University of Tarbiat Modares, 2014)
Mass generation of bagasse wastes from every 100 kg of sago starch pith being processed are likely to pollute the water when they are discarded into rivers. The increase of livestock production increases manure production and improper management of these manures will pollute the soil and environment, and causing diseases outbreak. Co-composting of sago bagasse and chicken manure could serve as a viable alternative of managing these wastes. In order to reduce pollution, the objective of this study was to co-compost sago bagasse and chicken manure slurry to obtain a high quality organic fertilizer. The sago bagasse was thoroughly mixed with chicken manure slurry, chicken feed, and molasses in polystyrene boxes. Co-compost temperature readings were taken 3 times daily. Nitrogen and P concentrations increased (1.46 and 0.12%, respectively), whereas C content decreased (48.6%) throughout the co-composting. The CEC increased from 45.7 to 68.3 cmol kg-1 indicating humified organic material. By the end of co-composting, humic acid and ash contents also increased from 7.3 to 10.0% and 7.1 to 11.6%, respectively. The pH of the co-compost increased from 4.78 to 7.21. The final co-compost had no foul odour, but it had low heavy metals content, and a desired amount of nutrients. Seed germination indices of phytotoxicity test were above 80% of final co-compost. Co-compost product with balanced nutrients content can be produced by co-composting sago bagasse and chicken manure slurry.